Association between alcohol consumption and latent fasting blood glucose trajectories among midlife women - Wang, Xingzhou; Lin, Song; Wang, Xiwei; Gao, Pengxia; Chen, Juan (Frontiers in Public Health, 2024)
Background This investigation sought to elucidate the correlations between alcohol intake and trajectories of fasting blood glucose (FBG) among American women in midlife. Methods Our analysis was rooted in the foundational data from the Study of Women’s Health Across the Nation (SWAN), a comprehensive longitudinal study centered on US women during their midlife transition. We employed group-based trajectory modeling to chart the FBG trajectories spanning from 1996 to 2005. Employing logistic regression, we gauged the odds ratios (ORs) and 95% confidence intervals (CIs) to draw connections between initial alcohol consumption and FBG trajectory patterns, whilst controlling for predominant potential confounders. Results Our cohort comprised 2,578 women in midlife, ranging in age from 42 to 52, each having a minimum of three subsequent FPG assessments. We discerned two distinct FBG trajectories: a low-stable pattern (n = 2,467) and a high-decreasing pattern (n = 111). Contrasted with the low-stable group, our data showcased an inverse relationship between alcohol intake and the high-decreasing FBG trajectory in the fully adjusted model 3. The most pronounced reduction was evident in the highest tertile of daily servings of alcoholic beverages (OR: 0.23, 95% CI: 0.10–0.52, p < 0.001), percentage of kilocalories sourced from alcoholic beverages (OR: 0.30, 95% CI: 0.16–0.58, p < 0.001), and daily caloric intake from alcoholic beverages (OR: 0.31, 95% CI: 0.16–0.62, p < 0.001). Conclusion Moderate alcohol consumption may protect against high FPG trajectories in middle-aged women in a dose–response manner. Further researches are needed to investigate this causality in midlife women.